Thriving in place: Multidimensional neighborhood typologies and cognitive function among U.S. older adults in the Health and Retirement Study - Jiao Yu; Weidi Qin; Jiuzhou Wang; Eva Kahana (PLoS ONE, 2026)
Background Neighborhood physical, social, and service environments are increasingly recognized as important contextual factors related to cognitive health; however, few studies have examined how these features collectively shape cognitive outcomes. This study aimed to classify neighborhood typologies based on a constellation of neighborhood features and to investigate their associations with cognitive function among U.S. older adults. Methods We conducted a cross-sectional analysis of 6,480 participants from the 2016 wave of the Health and Retirement Study. To examine contemporaneous associations, neighborhood features were derived from the 2015 National Neighborhood Data Archive, including measures of neighborhood deprivation, service facilities, food access, healthcare facilities, and environmental hazards. Cognitive function was assessed using the 27-point Telephone Interview for Cognitive Status (TICS). The Partitioning Around Medoids (PAM) clustering algorithm was used to classify neighborhood typologies. Multilevel regression models were performed to examine the associations between neighborhood typologies and cognitive function, with individuals as the first level and census tracts as the second level. Results Four neighborhood typologies were identified based on the elbow method and theoretical interpretability: (1) low deprivation, green neighborhood, (2) mid-SES, high hazard neighborhood, (3) high-amenity neighborhood, and (4) disadvantaged neighborhood. Regression results revealed significant disparities in cognitive function across neighborhood typologies. Compared to those living in disadvantaged neighborhoods, older residents in high-amenity neighborhoods characterized by extensive facilities and cognitively stimulating services demonstrated better cognitive function ( β = 3.85 , 95% CI: 1.23–6.47), after adjusting for individual-level characteristics. Conclusions The identified neighborhood typologies reveal an unequal distribution of amenities and hazards, which may help explain considerable inequities in late-life cognitive health. Tailored community initiatives addressing amenity availability and environmental hazards could be pivotal in promoting cognitive health and supporting aging in place.